Microcontroller for PWM inverter / Mustapa Epit - Epit, Mustapa (1997)
In this a three phase microcontroller pulse width modulation (PWM) tranststars inverter has been introduced. The PWM control signals are produced using a software in PC, so that me complex control circuit hardware of the inverter can be replaced by the software. The PWM switching strategy is proposed, which is closety approximates and exhibits many of the desirable performance characteristics of optimized PWM strategies based on minimized the total harmonics distortion. The drive system hardware includes the implementation of PC control system, transistor inverter, interface circuits, and driving circuits. The transistors are used as efficient switching devices for the inverter power circuits. The PWM inverter is designed to feed an induction motor with the adjustable frequency. Variable frequency output is generated by varying the width of PWM pulses biasing the transistors of the inverter. This is achieved when the computer generated the pulses through the interface to the inverter. This computer are links to the various sub-system to control the speed of the three phase induction motor.